HUBUNGAN SEKS BEBAS DENGAN KEJADIAN SIFILIS DI WILAYAH KERJA PUSKEMAS KOM YOS SUDARSO KOTA PONTIANAK - Dj, Herlinda Djohan; Sutriswanto, Sutriswanto; Nurhayati, Etiek; Ratika, Meila; Salim, Maulidiyah (Jurnal Laboratorium Khatulistiwa, 2024)
Syphilis, also known as "the lion king", is an STI (Sexually Transmitted Infection), a disease caused by infection with the Treponema Pallidum bacteria. It is chronic and chronic. This is a dangerous disease because it can attack all organs of the body. This research was conducted at the Kom Yos Sudarso Pontianak Community Health Center because the Community Health Center is a referral health center for syphilis examinations and the respondents were people who were caught by field officers who allowed free sex.               This study aims to find out who suffers from syphilis among respondents who engage in casual sex, as well as finding out the percentage of syphilis incidents in people who engage in casual sex and to find out the relationship between casual sex and the incidence of syphilis in the work area of the Kom Yos Sudarso Community Health Center, Pontianak City.               This research design uses cross sectional with random sampling technique. The samples used were 123 patient blood samples using the TP Rapid method.               Based on the results of the research conducted, casual sex and the incidence of syphilis were obtained. The results of analysis using the chi square test using Continuity Correctionb obtained a value of p = 0.021 < 0.05, so HA was accepted so that there was a significant relationship between casual sex and the incidence of syphilis in the work area of the Community Health Center. Yos Sudarso, Pontianak City.